Live-cell imaging to measure BAX recruitment kinetics to mitochondria during apoptosis - Maes, Margaret E. (PLoS One, 2017)
The pro-apoptotic BCL2 gene family member, BAX, plays a pivotal role in the intrinsic apoptotic pathway. Under cellular stress, BAX recruitment to the mitochondria occurs when activated BAX forms dimers, then oligomers, to initiate mitochondria outer membrane permeabilization (MOMP), a process critical for apoptotic progression. The activation and recruitment of BAX to form oligomers has been studied for two decades using fusion proteins with a fluorescent reporter attached in-frame to the BAX N-terminus. We applied high-speed live cell imaging to monitor the recruitment of BAX fusion proteins in dying cells. Data from time-lapse imaging was validated against the activity of endogenous BAX in cells, and analyzed using sigmoid mathematical functions to obtain detail of the kinetic parameters of the recruitment process at individual mitochondrial foci. BAX fusion proteins behave like endogenous BAX during apoptosis. Kinetic studies show that fusion protein recruitment is also minimally affected in cells lacking endogenous BAK or BAX genes, but that the kinetics are moderately, but significantly, different with different fluorescent tags in the fusion constructs. In experiments testing BAX recruitment in 3 different cell lines, our results show that regardless of cell type, once activated, BAX recruitment initiates simultaneously within a cell, but exhibits varying rates of recruitment at individual mitochondrial foci. Very early during BAX recruitment, pro-apoptotic molecules are released in the process of MOMP, but different molecules are released at different times and rates relative to the time of BAX recruitment initiation. These results provide a method for BAX kinetic analysis in living cells and yield greater detail of multiple characteristics of BAX-induced MOMP in living cells that were initially observed in cell free studies.